Depression Levels of University Students and Changes in their Nutritional Status in the COVID-19 Pandemic Quarantine Period: A study in Turkey - Baygut, Hatice (Progress in Nutrition, 2022)
Abstract: Objective: The objective of this study was to examine the depression levels and nutritional changes of university students during the COVID-19 pandemic quarantine process. Method: A cross-sectional study was conducted in 4528 university students, aged between 18-42 years, living in Turkey. A questionnaire form questioning demographic characteristics, anthropometric measurements, dietary changes and BECK Depression Inventory was sent to the university students via the online system (via google form). Analysis results are presented as mean ± standard deviation and median (minimum – maximum) for quantitative data, and categorical data are presented as frequency (percentage). Results: There was a statistically significant relationship between gender and the BDI score (p<0.001). A statistically significant difference was found between the distributions of general nutritional change in women compared to the BDI groups (p<0.001). Risk factors affecting nutritional changes were analyzed by binary logistic regression analysis as univariate and multivariate models. According to the Univariate model result, the risk of nutritional changes increases 1.042 times when the BDI score increases (p<0.001). The risk of nutritional changes of women is 1.618 times higher than that of men (p<0.001). When the results of the multivariate model are examined, the risk of nutritional changes increases 1.038 times when the BDI score increases (p<0.001). The risk of nutritional changes of women is 1.339 times higher than that of men (p<0.001). Conclusion The quarantine period caused some changes in the nutritional changes and depression levels of university students. As a result, in this study conducted with university students, differences in food preferences and the presence of depressive state were observed during the COVID-19 pandemic quarantine period. It is necessary to be aware of what university students are going through in this period and to take preventive measures to improve their health. Keywords: COVID-19, university students, nutrition, foods, depression